1994
DOI: 10.1165/ajrcmb.10.6.8003342
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of lung injury induced by microbial products: implication of tumor necrosis factor.

Abstract: Mice of the C57BL/6 strain were injected with bacterial lipopolysaccharide (LPS) followed by formylnorleucyl-leucyl-phenylalanine (FNLP) by the intraperitoneal route; markers of acute lung injury were examined in mice given a fusion protein of soluble human tumor necrosis factor-alpha (TNF-alpha) receptor (p80) linked to the Fc portion of human IgG (TNFR:Fc) or excipient. Challenge with LPS/FNLP elicited an adult respiratory distress syndrome-like pathology characterized by sharp increases in levels of lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Thus, we directly administered TNF-␣ by the intranasal route, and we demonstrated that, similarly to LPS exposure, TNF-␣ administration induced airway neutrophilia, enhanced MMP-9 activity, and reduced the IL-10 level in BALF. These results are consistent with data demonstrating that TNF-␣ favored neutrophil sequestration and migration (Ulich et al, 1993;Denis et al, 1994;Goncalves de Moraes et al, 1996) and that the difference in the levels of TNF-␣ and IL-10 modulates cell recruitment. Interestingly, a 30 mg/kg RP 73-401 pretreatment partially but significantly reduced airway neutrophilia and enhanced significantly IL-10 release but did not reduce MMP-9 activity in BAL of TNF-␣-exposed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we directly administered TNF-␣ by the intranasal route, and we demonstrated that, similarly to LPS exposure, TNF-␣ administration induced airway neutrophilia, enhanced MMP-9 activity, and reduced the IL-10 level in BALF. These results are consistent with data demonstrating that TNF-␣ favored neutrophil sequestration and migration (Ulich et al, 1993;Denis et al, 1994;Goncalves de Moraes et al, 1996) and that the difference in the levels of TNF-␣ and IL-10 modulates cell recruitment. Interestingly, a 30 mg/kg RP 73-401 pretreatment partially but significantly reduced airway neutrophilia and enhanced significantly IL-10 release but did not reduce MMP-9 activity in BAL of TNF-␣-exposed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, high levels of TNF-a have been correlated with the severity of pathological disturbances caused by endotoxin (Tracey et al, 1986;Gorgen et al, 1992). Once released, TNF-a favours the migration and sequestration of neutrophils which play a critical role in the pathogenesis of lung inflammation (Ulich et al, 1991;Deni et al, 1994;Steinberg et al, 1994), including adult respiratory distress syndrome (ARDS). The increased adherence of neutrophils to endothelial cells induced by TNF-a leads to their massive infiltration in pulmonary spaces (Albelda et al, 1994;Ulich et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a toxic biological substance that initiates acute inflammation, can produce experimental acute lung injury (ALI) [1][2][3] resulting in hypoxemia. Ongoing exposure to hypoxemia/hypoxia induces death of lung cells, which are vulnerable to hypoxic conditions; hypoxia further increases lung inflammation after LPS exposure.…”
mentioning
confidence: 99%